Non-covalent nanodiamond–polymer dispersions and electrostatic immobilization of bovine serum albumin protein. (13th November 2015) - Skaltsas, T; Pispas, S; Tagmatarchis, N
Abstract: Nanodiamonds (NDs) lack efficient dispersion, not only in solvents but also in aqueous media. The latter is of great importance, considering the inherent biocompatibility of NDs and the plethora of suitable strategies for immobilizing functional biomolecules. In this work, a series of polymers was non-covalently interacted with NDs, forming ND–polymer ensembles, and their dispersibility and stability was examined. Dynamic light scattering gave valuable information regarding the size of the ensembles in liquid phase, while their morphology was further examined by high-resolution transmission electron microscopy imaging. In addition, thermal analysis measurements were applied to collect information on the thermal behavior of NDs and their ensembles and to calculate the amount of polymer interacting with the NDs, as well as the dispersibility values of the ND–polymer ensembles. Finally, the bovine serum albumin protein was electrostatically bound to a ND–polymer ensemble in which the polymeric moiety was carrying quaternized pyridine units.